1995
DOI: 10.2172/34319
|View full text |Cite
|
Sign up to set email alerts
|

Innovative grout/retrieval demonstration final report

Abstract: Work performed under DOE Contract NO. DE-AC07-94D13223 DISTRIBUTION OF THIS DOCU!JEKf I S UNLlMiTED i DISCLAIMER This repon was prepared as an account of work sponsored by an agency of the United States Government. Neitherthe United States Government nor any agency thereof, nor any of their employees, makes any warranty, express or implied. or assumes any legal liability or responsibility for the accuracy. completeness, or usefulness of any information, apparatus, product or process disclosed. or represents th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, with the DAVY KENT drilling system, even in the relatively loose soils of the debris pi~it took excessive time to drill, resulting in excess drilling fluid pouring from the hole. Nevertheless, using the 4s per step interval, a series of four adjacent holes (1,2,3, and 4 on the thrust blockaee Figure 20) were grouted in the soil part of the debris pit with encouraging results. The amount of grout returns for drilling all four holes within a single joist of a thrust block did not fill the joist under the holes being grouted nor was there an excessive amount of grout collected under other joists (presumably by drainage through leakage paths caused by the imperfect seal between the thrust block joists and the sublayer of pea gravel).…”
Section: Etieet Of Soil Type On Groutabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, with the DAVY KENT drilling system, even in the relatively loose soils of the debris pi~it took excessive time to drill, resulting in excess drilling fluid pouring from the hole. Nevertheless, using the 4s per step interval, a series of four adjacent holes (1,2,3, and 4 on the thrust blockaee Figure 20) were grouted in the soil part of the debris pit with encouraging results. The amount of grout returns for drilling all four holes within a single joist of a thrust block did not fill the joist under the holes being grouted nor was there an excessive amount of grout collected under other joists (presumably by drainage through leakage paths caused by the imperfect seal between the thrust block joists and the sublayer of pea gravel).…”
Section: Etieet Of Soil Type On Groutabilitymentioning
confidence: 99%
“…For the limited amount of holes grouted in the soil pit (holes 1,2,14,15,18,19,22, 23-see Figure 20), smear samples were taken for holes 1, 18, 19, and 22, with the result that large amounts of molybdenum tracer were found in the grab samples of grout under the thrust block and on the drill stem following grouting of a hole. However, very little tracer was found in smears of the surface of the thrust block or in the filters for the high-volume air samplers.…”
Section: Soil Pitmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 10% (visual determination) of the monolith volume contained irregularly shaped pockets t10.2 cm diameted30.5 cm length (4 in. diameterll Et length)] of moist soil that were not stabilized or solidified (Loomis and Thompson, 1995). Although it was observed that these pockets of soil were completely encapsulated and there were no apparent conduits for water transmission, these pockets of untreated soil could potentially be released should the monolith become fractured.…”
Section: !mentioning
confidence: 99%
“…Similarly, loose debris (cloth, paper, wood, and small metal) apparently weakened the monolith as demonstrated by the relative ease in which the portion of the monolith that contained debris could be retrieved. It was also observed that when retrieved, encapsulating grout easily broke off of the loose debris, leaving the debris surface exposed to air (Loomis and Thompson, 1995). Should in situ stabilization be conducted at the FBRP, the type of S/S reagent delivery system used may depend primarily upon the type of S / S reagent and recipe that is to be used since the reagent must be amenable to the reagent delivery system.…”
Section: !mentioning
confidence: 99%